Penguatan Analisis Lingkungan Internal (ALI) dan Analisis Lingkungan Eksternal (ALE) di Lembaga Pendidikan Islam dalam Menghadapi Era Disrupsi - Ahmad Mihdad Mahda Fiqia; Chusnul Chotimah; Sulistyorini (Southeast Asian Journal of Islamic Education Management, 2023)
This study aims to describe analysis of internal and external environment of SDIT Al-Azhaar in facing the era of disruption, in order to survive. The method used in this research is descriptive qualitative method. Data collection techniques using semi-structured interviews, semi-participant observation, and documentation. The analysis techniques used include data collection, data condensation, data presentation, and drawing conclusions. The results of this study indicate: 1) SDIT's internal environment analysis consists of competency aspects in the form of quality educational institutions that are already good, core competencies in the form of SDIT Al-Azhaar's contribution to Trenggalek district by sending students to competitions, resource aspects dominated by teachers with graduates S1, and BOS funding which can be said to be large enough to optimize existing learning activities, 2) external environmental analysis, namely SDIT Al-Azhaar always seeks to collaborate with existing stakeholders, establish cooperation with external organizations, have a role and support local government towards SDIT Al-Azhaar in increasing school quality competition, 3) efforts to strengthen the internal environment are carried out at SDIT Al-Azhaar by utilizing digital-based learning media, each educator is given insight regarding the use of technology, communicating with guardians using smartphone media, 4) strengthening The external environment is carried out by holding periodic socialization with the community and stakeholders, using media for promotional activities and updating activities within the school scope, using technology in the facilities and infrastructure used. This strengthening effort was carried out as a preparation for students to be able to face the era of disruption.